2014
DOI: 10.1089/ees.2013.0392
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Transport of Graphene Oxide Nanoparticles in Groundwater and Surface Water

Abstract: The effects of groundwater and surface water constituents (i.e., natural organic matter [NOM] and the presence of a complex assortment of ions) on graphene oxide nanoparticles (GONPs) were investigated to provide additional insight into the factors contributing to fate and the mechanisms involved in their transport in soil, groundwater, and surface water environments. The stability and transport of GONPs was investigated using dynamic light scattering, electrokinetic characterization, and packed bed column ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 70 publications
1
65
0
Order By: Relevance
“…It has been successfully used in a wide range of fields, including energy storage, nanoelectronic devices, batteries, transparent conductors, and environmental protection (Geim and Novoselov, 2007;Wang et al, 2010). Recent studies indicated that graphene and graphene-based materials are stable and can travel long distances in the environment (Lanphere et al, 2014). Therefore, with their increasing use, they might ultimately be released into the aquatic, terrestrial, and atmospheric environments, where their ecological risks are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been successfully used in a wide range of fields, including energy storage, nanoelectronic devices, batteries, transparent conductors, and environmental protection (Geim and Novoselov, 2007;Wang et al, 2010). Recent studies indicated that graphene and graphene-based materials are stable and can travel long distances in the environment (Lanphere et al, 2014). Therefore, with their increasing use, they might ultimately be released into the aquatic, terrestrial, and atmospheric environments, where their ecological risks are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These also reduce the degree of control on size and morphology of the graphene and increase the cost of the process. Recent report on environmental impact of nanomaterials has raised serious concern about this kind of chemically treated graphene [19]. It is therefore, imperative to develop a better process to produce graphene with high yield, but without the use of chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that graphene materials are stable and can spread over long distances in the environment [3]. Therefore, owing to their widespread use, it is important to assess the potential risks associated with their release into the environment and the consequent interactions with organisms.…”
mentioning
confidence: 99%